Social-Cultural Factors And Coffee Consumption In Rukungiri District,Uganda. - Turyasingura, John Bosco; Moses, Agaba (Quest Journals, Journal of Research in Business and Management, 2023)
This study adopted a cross-sectional survey research design and involved quantitative and qualitative methods which enabled the study to evaluate the relationship between the study variables in a snapshot. A sample of 123 respondents was selected using simple random and purposive sampling techniques. The quantitative data were analyzed using SPSS Version 23.0 and the thematic analysis method was used to analyze the qualitative data. Quantitative results in form of descriptive statistics, correlations and regressions were presented in tables based on the study objectives. The study found that social-cultural factors were positively and significantly related to coffee consumption (r =. 764, P≤.01). The social-cultural factors status in terms of Social class of people/reference groups, Occupation and Life Style and as such, coffee consumption is influenced by these factors. The study further concluded that embedded beliefs, that the people of Rukungiri District should go back to their tradition of coffee consumption since it was their own from the beginning